Неолітизація Київського Подніпров’я у світлі нових досліджень - Залізняк, Л.Л.; Сорокун, А.А.; Переверзєв, С.В.; Хоптинець, І.М. (Археологія, 2016)
Статтю присвячено проблемам поширення найдавнішої кераміки та навичок відтворювального господарства на Київщині. Перші неолітичні новації в регіоні зафіксовано в матеріалах пам’яток типу Лазарівка з кременем кукрецького типу та керамікою, що мають прямі паралелі в старожитностях буго-дністровської культури Південного Бугу. The issue of the Neolithization of Kyiv Dnipro region is being considered at a background of the Neolithic raising in Ukraine. Kukrek type flint industry and original Neolithic pottery having direct parallels in Buh-Dnister culture in the Buh River region are peculiar for the earliest Neolithic sites of Lazarivka type in Kyiv region. Based on earlier known and newly obtained materials, the authors come to the conclusion about the leading role of influences from the Balkan-Danube Neolithic in the Neolithization of the Right-Bank Ukraine and the Dnipro River middle region. The Right-Bank Ukraine Neolithization took part in the 6th millennium BC as a result of four waves of Neolithic migrants from the Danube River region. The Hrebenyky traditions bearers were the first proto-Neolithic wave of migrants from the Balkans who left the sites of the same name culture in Odesa region of the 7th and the beginning of the 6th millennia BC (саl.). Flint inventory of this culture has direct parallels in the materials of the early Neolithic in Thessaly, as well as in flint assemblages of Krish culture. The Krish culture population played a notable role in the Neolithization of Ukraine. Moving from Transylvania to the east in the second quarter of the 6th millennium BC, they reached Dnister region where they are represented by Sakarovka type sites. Owing to the synthesis of Krish Neolithic and local Kukrek traditions in about the middle of the 6th millennium BC, BuhDnister culture, the oldest Neolithic culture of Ukraine, appeared. The population of Danube culture (Linear Pottery culture or LPC) can be called the third wave of Neolithic migrants into the Right Bank Ukraine; it moved from the Visla River upper region to Volyn, and to the Dnister River upper region, to Moldova, and to the region between the Buh and Dnister Rivers from there. The pressure of new Neolithic migrants from the west upon the Buh-Dnister population led to its movement in the north-eastern direction, into Dnipro River region of Kyiv and Cherkasy and perhaps into Nadporizzhia. These very processes of the second half of the 6th millennium BC led the beginning of the Neolithization of the Dnipro River middle region, including Kyiv Polissya. Buh-Dnister population migration into Dnipro River region of Kyiv and Cherkasy especially strengthened at the end of the 6 th millennium BC as a result of powerful pressure from the fourth wave of the Balkan-Danubian colonists, Cucuteni-Trypillya culture population, which started from Moldova territory the agricultural colonization of the Forest-Steppe zone between the Dnister and the Dnipro Rivers at this period. A final victory of producing economy in Right Bank Ukraine is related exactly with the Trypillians. Overwhelming majority of the researchers believe that the Neolithization of the Danube River region and of Central Europe took part in procedure of their «Balkanization», in other words, spread of Neolithic innovations from the Balkans via the Danube Region took part by means of migrations of the Neolithic colonists to the north. It was colonization regime, in which the bearers of Hrebenyky, Danube (LPC), Buh-Dnister, and Cucuteni-Trypillya cultures spread in Right Bank Ukraine. На фоне формирования неолита Украины рассматривается проблема неолитизации Киевского Поднепровья. Для древнейших неолитических памятников Киевщины типа Лазаревка характерно наличие кремня кукрекского типа и своеобразная неолитическая керамика, которые имеют прямые параллели в неолите буго-днестровской культуры Побужья. На основе ранее известных и вновь полученных материалов авторы приходят к выводу о ведущей роли влияний балкано-дунайского неолита в процессе неолитизации Правобережной Украины и Среднего Поднепровья. Неолитизация Правобережной Украины произошла вследствие четырех волн неолитических мигрантов с Подунавья. Первой протонеолитической волной мигрантов с Балкан были носители гребениковских традиций, которые оставили в Одесском регионе памятники одноименной культуры конца VIІ — начала VI тис. ВС (саl.). Кремневый инвентарь последней имеет прямые параллели в материалах раннего неолита Фессалии, а также в кремневых комплексах культуры Крыш. Носители последней сыграли особенно заметную роль в неолитизации Украины. Продвигаясь с Трансильвании на восток во второй четверти VI тис. ВС, они достигли Приднестровья, где представлены памятниками типа Сакаровка. Вследствие синтеза кришских неолитических традиций с местными кукрекскими около середины VI тис. ВС возникла древнейшая неолитическая культура Украины — буго-днестровская. Третьей волной неолитических мигрантов на Правобережную Украину можно считать население дунайской культуры (КЛЛК), которое в третьей четверти VI тис. ВС продвинулось с верховьев Вислы на Волынь, а оттуда — на Верхний Днестр, в Молдову и в буго-днестровское междуречье. Давление с запада новых неолитических переселенцев на буго-днестровское население привело к его движению в северо-восточном направлении — в КиевоЧеркасское Поднепровье, и похоже в Надпорожье. Именно эти процессы второй половины VI тис. ВС положили начало неолитизации Среднего Поднепровья, в том числе Киевского Полесья. Переселение буго-днестровцев в Киево-Черкасское Поднепровье особенно усилилось в конце VI тис. ВС вследствие мощного давления со стороны четвертой волны балкано-дунайских колонистов — населения культуры Кукутени-Триполье, которое в это время с территории Молдавии начало земледельческую колонизацию лесостепей между Днестром и Днепром. Окончательную победу производящей экономики на Правобережной Украине связывают именно с трипольцами. Подавляющее большинство исследователей считает, что неолитизация Подунавья и Центральной Европы произошла в режиме их «балканизации», то есть распространение неолитических новшеств с Балкан через Подунавье путем расселения неолитических колонистов на север. Именно в режиме колонизации распространялись на Правобережной Украине носители культур Гребеники, дунайской (КЛЛК), буго-днестровской, Кукутени-Триполье.